2017
DOI: 10.1111/pce.12981
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ketoacyl‐CoA synthase 16 (KCS16) forms C36/C38 acyl precursors for leaf trichome and pavement surface wax

Abstract: The aliphatic waxes sealing plant surfaces against environmental stress are generated by fatty acid elongase complexes, each containing a β-ketoacyl-CoA synthase (KCS) enzyme that catalyses a crucial condensation forming a new C─C bond to extend the carbon backbone. The relatively high abundance of C and C alkanes derived from C and C acyl-CoAs in Arabidopsis leaf trichomes (relative to other epidermis cells) suggests differences in the elongation machineries of different epidermis cell types, possibly involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Phenotypic observations and SEM analysis revealed that the density of trichomes on the leaves and stems of transgenic Arabidopsis was significantly higher than that of the WT plants ( Figures 5 , 6 , 8 ), suggesting CsKCS6 might be involved in the development of trichomes. To our surprise, although AtKCS16 is proved to catalyze the elongation of C 34 to C 38 acyl-CoAs in Arabidopsis leaf trichomes ( Hegebarth et al, 2017 ), none of the KCS6 homologous genes and other KCS family genes were reported to be related to trichome formation ( Fiebig et al, 2000 ; Hooker et al, 2002 ; Serra et al, 2009 ; Weidenbach et al, 2015 ). The divergence between our result and previous reports is probably attributed to the gene function difference among plant species.…”
Section: Discussionmentioning
confidence: 88%
“…Phenotypic observations and SEM analysis revealed that the density of trichomes on the leaves and stems of transgenic Arabidopsis was significantly higher than that of the WT plants ( Figures 5 , 6 , 8 ), suggesting CsKCS6 might be involved in the development of trichomes. To our surprise, although AtKCS16 is proved to catalyze the elongation of C 34 to C 38 acyl-CoAs in Arabidopsis leaf trichomes ( Hegebarth et al, 2017 ), none of the KCS6 homologous genes and other KCS family genes were reported to be related to trichome formation ( Fiebig et al, 2000 ; Hooker et al, 2002 ; Serra et al, 2009 ; Weidenbach et al, 2015 ). The divergence between our result and previous reports is probably attributed to the gene function difference among plant species.…”
Section: Discussionmentioning
confidence: 88%
“…Our results indicate that several n-alkane synthesis complexes are required to carry out the production of the very broad range of chain lengths in alkanes found in plants, from 25 up to 37 carbon atoms in leaves of Arabidopsis, for example (Bernard and Joubès, 2013;Hegebarth et al, 2017). A variety of other organisms such as bacteria, yeasts, fungi, insects, and microalgae can convert fatty acids into hydrocarbons; nevertheless, enzymes involved in alka(e)ne biosynthesis are not conserved across kingdoms, and a wide variety of pathways for hydrocarbon biosynthesis have been identified in recent years (Fu et al, 2015;Jiménez-Díaz et al, 2017).…”
Section: Plantmentioning
confidence: 88%
“…Initially, indirect evidence came from SEM investigations of Arabidopsis stem surfaces. It had repeatedly been reported that the surface of stem pavement cells is covered with epicuticular wax crystals [ 33 , 34 , 35 , 36 , 37 ], while the surface of stem trichomes was devoid of crystals [ 6 , 7 , 38 ]. It is well established that epicuticular wax crystals form due to the accumulation of one or a few compounds in the wax mixture, and the absence or presence of crystals, hence, reflects different amounts of the crystal-forming compounds within the overall wax mixture [ 39 , 40 ].…”
Section: Composition Of Cuticular Wax Covering Arabidopsmentioning
confidence: 99%